Buckling initiation and propagation in pipes under external pressure. (15th December 2022) - Li, Tao; Xie, Peng; Li, Xiaotian
Abstract: A universal plastic ring-beam model is presented considering the longitudinal stretching effect in the transition zone based on the pipes' deformation mode analysis. An improved ring model is applied to the pipe's propagation pressure problem. The closed-form solutions are significantly improved compared to previous studies and are much closer to the FEM or experimental results, especially for medium-thick or thin-walled pipes. The proportion of longitudinal stretching effect in propagation pressure decreases with the increase of diameter-thick-ratio, accounting for 20%–30% of thin wall pipes (25≤ D/t ≤ 40), and 30%–40% for medium-thick-walled pipe (15≤ D/t ≤ 25). Buckling triggers simultaneously in the multiple equal ovalities along the pipe's axial direction. Oval defect deviation angle leads to generating torsional moments in the propagation buckling process, which in turn produces a flip phenomenon, propagation flip-flop mode occurs when the defect deviation angle is a right angle. Whether multipoint trigger mode, flip-flop mode or other axial factors of oval defects in pipes affect buckling initial pressure to different degrees but seem to have no effect on the propagation pressure. Highlights: A universal plastic ring-beam model is presented considering longitudinal stretching effect in transition zone. Pipes propagation pressure closed-form solution are correlate well with numerical and experimental results. Buckling propagation multipoint trigger and flip-flop mode are discussed. Effects of axial multi-oval defects on pipes buckling and propagation is discussed.